Combination of Piper betel Leaves and Areca catechu Nuts Ethanolic Extract Effects on In Vitro Antimicrobial Test against Aerobic Mouth Microbiota - Christanto, Raymond; Andre, Andre; Foustine, Shania; Hartiadi, Leonny Yulita (Indonesia International Institute for Life Sciences, 2019)
Introduction: Oral health awareness in Indonesia is still low with more and more oral and/or dental infection becomes more prevalent such as gingivitis, endodontitis, and pericoronitis. These infections could be caused by mouth microflora such as lactobacilli, Streptococcus mutans, Streptococcus mitis, Streptococcus oralis, and Streptococcus sobrinus. As time goes by, these bacteria could also become more problematic as antibacterial resistance emerges. Betel nut and betel leaf are well known traditional herbs that is often used in combination for